2021
DOI: 10.26434/chemrxiv-2021-34qmm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enzyme-Like Hydroxylation of Aliphatic C–H Bonds From an Isolable Co-Oxo Complex

Abstract: Selective hydroxylation of aliphatic C–H bonds remains a challenging but broadly useful transformation. Nature has evolved systems that excel at this reaction, exemplified by cytochrome P450 enzymes which use an iron-oxo intermediate to activate aliphatic C–H bonds with k1 > 1400 s–1 at 4 °C. Many synthetic catalysts have been inspired by these enzymes and are similarly proposed to use transition metal-oxo intermediates. However, most examples of well-characterized transition metal-oxo species are not capab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…1 Compared with emerging scorpionate ligands, classic tris(pyrazolyl)borates are relatively weak electron donors, 11 a limitation when studying high-valent reactive metals. 12 Tris(2-pyridyl)borate ligands were recently introduced by the Jakle laboratory as a new scorpionate ligand family distinguished both by their highly electron-donating properties and by their exceptional chemical and thermal resilience. 13 On this basis, our laboratory is interested in applying metal tris(2pyridyl)borates as catalysts for polymerization, an application that benefits from well-defined catalysts 14 but typically requires high temperatures industrially.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1 Compared with emerging scorpionate ligands, classic tris(pyrazolyl)borates are relatively weak electron donors, 11 a limitation when studying high-valent reactive metals. 12 Tris(2-pyridyl)borate ligands were recently introduced by the Jakle laboratory as a new scorpionate ligand family distinguished both by their highly electron-donating properties and by their exceptional chemical and thermal resilience. 13 On this basis, our laboratory is interested in applying metal tris(2pyridyl)borates as catalysts for polymerization, an application that benefits from well-defined catalysts 14 but typically requires high temperatures industrially.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We recently reported an adamantyl (Ad) substituted Co III -oxo complex, PhB( Ad Im)3Co III O, which, given the greater electron donating properties of the Ad groups, is more basic than our previous Co III -oxo complex. 77 Here we demonstrate that this enhanced basicity leads to more highly imbalanced CPET reactivity with C-H substrates. Exploration of activity with acidic phenol substrates reveals a switch from imbalanced CPET to stepwise reactivity featuring initial PT.…”
Section: Introductionmentioning
confidence: 65%
“…We have previously demonstrated that 1 Ad is more basic and more reducing than 1 tBu , as expected based on the more electron-donating Ad substituents on the imidazol-2-ylidene ligand scaffold. 77 Additionally, the BDFE of 1 Ad is larger than that measured for 1 tBu , providing additional driving force for H-atom abstraction. As 1 tBu Scheme 2.…”
Section: Results and Discussion C-h Activation Reactivity Of Phb( Ad ...mentioning
confidence: 96%
See 1 more Smart Citation
“…), and its change along the reaction pathway was shown to control uphill chemical processes (while downhill chemical reactions are typically controlled by a change in molecular hardness). 51 Since the initial C-H activation step is endergonic, 52 we compared  across all 7 nitrosamines (Table Lastly, we briefly considered the electrophilicity of all 7 nitrosamines, which plays an important role downstream in the covalent binding of DNA by alkylating metabolites (Figure 1). It is reasonable to propose that sufficient electronic 'signature' is present in the parent molecules to elucidate differential electrophilic reactivity of their metabolites.…”
Section: Esr Case Studymentioning
confidence: 99%